High workload is related to lower quality of life in public school teachers: A cross-sectional study - Da Silva, Claudiele C.M. [UNESP]; Beretta, Victor S. [UNESP]; Gil, Fernanda S. [UNESP]; Delfino, Leandro D. [UNESP]; Leite, Enrique G.F. [UNESP]; Ferrari, Gerson; Tebar, William R. [UNESP]; Christofaro, Diego G.D. [UNESP] (SAGE Publications, 2024)
BACKGROUND: People with long work hours, as evidenced by teachers, were more likely to present health problems that impact their quality of life (QoL). The reduced physical activity (PA) level or higher sedentary behavior in public school teachers was related to obesity. Although PA seems to improve the QoL in other professions, assessing whether the PA level could influence the relationship between workload and QoL in public school teachers is necessary. OBJECTIVE: To analyze whether the high workload was related to worse QoL in teachers considered less active and more active. METHODS: Two hundred forty-three teachers from public schools participated in this study. The domains of QoL and PA levels were assessed by SF-36 and Baecke questionnaires, respectively. Workload perception was assessed by a Likert scale. Binary logistic regression analyzed the association between high workload and QoL domains in teachers considering the PA level in a model adjusted by confounding factors (i.e., sex, age, and socioeconomic condition). RESULTS: Heavy workload was associated with less chances of having better physical limitation domain of both less and more physically active teachers. Less active teachers with heavy workloads were 53%, 61%, and 56% less likely to have better vitality, social functioning, and mental health, respectively. No such associations were observed in the more physically active teachers. CONCLUSION: Less active teachers with a heavy workload demonstrate lower QoL. Although the PA practice eliminated this relationship, both active and less active teachers with a heavy workload demonstrated lower QoL in physical limitation domain.
Keywords: adults; exercise; mental health; physical activity; quality of life; Teaching; workload